Development of Multiple Aortic Mycotic Aneurysms After Cardiac Catheterization - Desiree A. Steimer MD; John J. Squiers MD; J. Michael DiMaio MD; Katherine B. Harrington MD (SAGE Publishing, 2017)
A 71-year-old male with a past medical history of coronary artery bypass surgery developed multiple, infected pseudoaneurysms of the ascending aorta and aortic root 1 year after cardiac catheterization. He underwent aortic root replacement with a 24-mm homograft. Tissue culture from operative specimens revealed invasive Aspergillus fumigatus infection. He was treated with voriconazole for 3 months. After 1 year, he had no recurrence of symptoms, pseudoaneurysm, or fungal infection.